PENGEMBANGAN SERVIO MENGGUNAKAN FULL REST API UNTUK MENDUKUNG LAYANAN MULTIPLATFORM - ADE IVAN PRIYATNA IVAN; Hamdan Arfandy; Hendra Surasa (KHARISMA Tech, 2021)
The purpose of this research is to apply FullestAPI to the SERVIO that make it easier developing progress to other platform. This research uses the prototype method as a model for making web services that will be integrated with the SERVIO system. The results of the test show that the API is feasible to use based on research where the response time and data generated are directly proportional the more data sent need higher of the response time, for the number of requests simultaneously obtained a maximum of 30 requests at one time.